1980
DOI: 10.1113/jphysiol.1980.sp013531
|View full text |Cite
|
Sign up to set email alerts
|

selective elimination of motor nerve terminals in the rat soleus muscle during development.

Abstract: SUMMARY1. The pattern of innervation and either frequency of miniature end-plate potentials (m.e.p.p.s) or acetylcholine (ACh) sensitivity was examined in individual fibres of the soleus muscle in new-born rats to elucidate the mechanism of elimination of motor nerve terminals.2. The number of motor nerve terminals innervating a muscle fibre was judged by the difference in latencies of end-plate potentials evoked by stimulation of the ventral roots L4 and L5.3. At early developmental stages, about 50 % of sole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
4

Year Published

1981
1981
1996
1996

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 34 publications
(68 reference statements)
1
38
4
Order By: Relevance
“…1 A). These two features have often been adopted as an indication of multiple innervation (Redfern, 1970;Brown et al 1976;Miyata & Yoshioka, 1980). Multiple innervation could be recognized fairly readily by these methods in younger animals, but discrimination became difficult in older animals where motor axon thresholds were similar among innervating nerves (Rosenthal & Taraskevich, 1977).…”
Section: Chan-ge8 Of Innervation Patternmentioning
confidence: 99%
See 1 more Smart Citation
“…1 A). These two features have often been adopted as an indication of multiple innervation (Redfern, 1970;Brown et al 1976;Miyata & Yoshioka, 1980). Multiple innervation could be recognized fairly readily by these methods in younger animals, but discrimination became difficult in older animals where motor axon thresholds were similar among innervating nerves (Rosenthal & Taraskevich, 1977).…”
Section: Chan-ge8 Of Innervation Patternmentioning
confidence: 99%
“…In this study, we have focused on the following developmental changes in neuromuscular junctions: (a) the elimination of excess axons in polyneuronal innervation (Redfern, 1970;Bennett & Pettigrew, 1974;Brown, Jansen & Van Essen, 1976;Rosenthal & Taraskevich, 1977); (b) the increase in frequency of miniature end-plate potentials (m.e.p.p.s) (Diamond & Miledi, 1962;Kelly, 1978;Miyata & Yoshioka, 1980); (c) the reduction of extrasynaptic acetylcholine (ACh) sensitivity (Diamond & Miledi, 1962;Bevan & Steinbach, 1977;Miyata & Yoshioka, 1980); and (d) the shift from facilitation to depression of end-plate potentials (e.p.p.s) (Bennett & Pettigrew, 1974). These properties were investigated in normal, hypo-and hyperthyroid new-born rats and it was demonstrated that thyroid hormone is important for the normal maturation of neuromuscular synapses; the lack or excess of thyroid hormone retarded or accelerated the developmental changes in these properties, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Whether the histochemical properties of muscle fibers under multiple innervation are regulated by neuronal factors of the predetermined spinal motoneurons, the functional activity, and/or neurotrophic factors has been discussed in previous studies (THOMPSON et al, 1984;GORDON and VAN ESSEN, 1985;JONES et at., 1987a, b;FLADBY and JANSEN, 1988;REDENBACH et al, 1988). Although the mechanism underlying the type shift of muscle fibers under multiple innervation is not clear, our findings suggest that collateral sprouting from type-different motoneurons which differentiate earlier causes the type shift of muscle fibers during early postnatal development, as observed by MIYATA and YOsHIOKA (1980) All muscle fibers 1 day after birth showed a uniform reaction for the enzyme, but fast-twitch (dark) and slow-twitch (light) fibers were found at 9 days. Thereafter, the type shift of fibers from slow-twitch to fast-twitch was observed during postnatal development while multiply innervated (13 days).…”
Section: Discussionmentioning
confidence: 49%
“…Measurements of contractions show that the proportion of soleus muscle fibres innervated by axons from both L4 and L5 roots is as much as 80 % up to 8 days of age, and is reduced to less than 10 % by 14 days. This reduction is due almost exclusively to the loss of innervation by L4axons (see also Miyata & Yoshioka, 1980); in the present experiments this change in the pattern of innervation has been exploited to distinguish between potentially surviving (L5) and non-surviving (L4) nerve terminals.…”
Section: Pmentioning
confidence: 99%
“…of mean, n = 19 fibres) for L4 and 6-7 + 0 99 (n = 12) for L5. These values are the sums of the quantal release from all the activated nerve terminals at these immature end-plates; since there may be fewer axon terminals from L5 than from L4 (Miyata & Yoshioka, 1980), the observed difference in quantum content is probably an underestimate of the real difference between individual L4 and L5 terminals. Quantum size in magnesium-poisoned muscles was estimated from histograms of the e.p.p.…”
Section: Pmentioning
confidence: 99%